2011
DOI: 10.1016/j.ccr.2011.05.026
|View full text |Cite
|
Sign up to set email alerts
|

Targeting Androgen Receptor in Estrogen Receptor-Negative Breast Cancer

Abstract: Summary Endocrine therapies for breast cancer that target the estrogen receptor (ER) are ineffective in the 25-30% of cases that are ER negative (ER−). Androgen receptor (AR) is expressed in 60-70% of breast tumors, independent of ER status. How androgens and AR regulate breast cancer growth remains largely unknown. We find that AR is enriched in ER−breast tumors that over-express HER2. Through analysis of the AR cistrome and androgen-regulated gene expression in ER−/HER2+ breast cancers we find that AR mediat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

19
304
0
2

Year Published

2012
2012
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 332 publications
(325 citation statements)
references
References 58 publications
(76 reference statements)
19
304
0
2
Order By: Relevance
“…We and others have previously shown that MDA-MB-453 cells express very high levels of AR compared with other breast cancer cell lines, with the levels being comparable to those seen in the LNCaP prostate cancer cell line (Hall et al 1994, Birrell et al 1995, Lehmann et al 2011, Robinson et al 2011. Moreover, like prostate cancer cells, but in contrast to most AR(C), ER(C) breast cancer cell lines, proliferation of MDA-MB-453 cells is stimulated by androgens in an AR-dependent manner (Birrell et al 1995, Doane et al 2006, Naderi & Hughes-Davies 2008, Ni et al 2011. Recent studies have shown that AR signaling in MDA-MB-453 cells stimulates a forkhead box A1 (FOXA1)-dependent transcriptional program that is similar to that associated with estrogen signaling in ER(C) luminal breast cancers or cell line models of luminal disease (Doane et al 2006, Robinson et al 2011.…”
Section: Introductionmentioning
confidence: 60%
See 2 more Smart Citations
“…We and others have previously shown that MDA-MB-453 cells express very high levels of AR compared with other breast cancer cell lines, with the levels being comparable to those seen in the LNCaP prostate cancer cell line (Hall et al 1994, Birrell et al 1995, Lehmann et al 2011, Robinson et al 2011. Moreover, like prostate cancer cells, but in contrast to most AR(C), ER(C) breast cancer cell lines, proliferation of MDA-MB-453 cells is stimulated by androgens in an AR-dependent manner (Birrell et al 1995, Doane et al 2006, Naderi & Hughes-Davies 2008, Ni et al 2011. Recent studies have shown that AR signaling in MDA-MB-453 cells stimulates a forkhead box A1 (FOXA1)-dependent transcriptional program that is similar to that associated with estrogen signaling in ER(C) luminal breast cancers or cell line models of luminal disease (Doane et al 2006, Robinson et al 2011.…”
Section: Introductionmentioning
confidence: 60%
“…Recent studies have shown that AR signaling in MDA-MB-453 cells stimulates a forkhead box A1 (FOXA1)-dependent transcriptional program that is similar to that associated with estrogen signaling in ER(C) luminal breast cancers or cell line models of luminal disease (Doane et al 2006, Robinson et al 2011. Furthermore, AR signaling induces Wnt/b-catenin signaling in a manner that subsequently augments the Erbb2 pathway to promote proliferation in MDA-MB-453 cells (Ni et al 2011). These findings support the development of therapeutic strategies for ER(K) breast cancer that target the AR, particularly for tumors that possess a steroid receptor profile characteristic of apocrine breast cancer, i.e.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Ni et al (2011) showed that AR transcriptionally activates the Wnt and Her2 pathways in a ligand-dependent manner. This indicates a possible role for AR therapeutic targeting in Her2-positive breast cancer.…”
Section: Wntmentioning
confidence: 99%
“…Especially, functional cross talk between AR and HER2 signaling has been proposed in ER-negative/HER2-positive breast carcinomas (Naderi & Hughes-Davies 2008, Ni et al 2011. Naderi & Hughes-Davies (2008) demonstrated that growth stimulatory effect of heregulin, a ligand of HER1 and HER3, was inhibited by AR inhibitor flutamide in MDA-MB-453 cells.…”
Section: K Takagi Et Al: Klf5 In Breast Carcinomamentioning
confidence: 99%